The travel dream experience in pandemic times - Correia, A.; Moro, S.; Rita, P. (Anatolia, 2023)
This study was developed to understand how tourists feel after dreamed travel experiences ended up cancelled. The orchestra model that considers experiences as an intermingled process was applied to analyse the negative feelings experienced by tourists during these pandemic times. Through web scraping, over 40 thousand comments from 600 threads discussing the pandemic impact on tourists’ inability to concretize their dreams were extracted from the TripAdvisor forum. Those comments were subjected to data mining techniques, including the generation of topic modelling and analysis of sentiment scores across continents vis-à-vis reported cases and fatalities. Results suggested that despite the disillusion for not being able to travel, tourists were understanding and mostly concerned with the health of their peers.